Development of a Practical Kit and a Citizen Scientist Program for Learning Chemistry - HEE TING, WONG (Chemistry Teacher International, 2022)
Laboratory practical is an essential component for effective learning of science. Providing laboratory experience can be challenging for some rural schools with limited laboratory facilities. The situation was exacerbated when schools were closed due to the COVID-19 pandemic. This thesis reports a laboratory kit design based on the Standard Curriculum for Secondary Schools in Malaysia (Kurikulum Standard Sekolah Menengah, KSSM). The kit was evaluated by students and experienced teachers from town and rural schools. Pre- and post-test was conducted with the students before and after using the kit. A questionnaire was disseminated to appraise the students’ perceptions on practical learning. There was a significant improvement (p < 0.05) in the overall score of the post-test (90.32) compared to the pre-test (71.00). Both rural and town schools demonstrated a significant increase in the overall mean scores, from 68.67 and 73.34 in the pre-test to 91.34 and 89.33 in the post-test. There was also improvement in affection for chemistry among students after using the kit. The practical kit can be deployed in schools with laboratory constraints and to be used outside the school settings. It was designed to be affordable compared to traditional lab setting, safe and environmental-friendly due to minimal chemical used, and providing individualized hands-on exposure. Besides, this thesis also reports a citizen science program on household food waste for students to introduce the idea of citizen science to them and to evaluate their learning experience. The project focused on quantification of avoidable solid food wastes in the households using the food waste diary. The results were positive, that is more than 80% of the participants agreed that this program increased their interest in chemistry learning, raised awareness of food waste reduction and waste management, and improved scientific skills such as food waste measurement.